Internalisasi Konsep Keadilan dan Maslahah dalam Pendidikan Ekonomi - Nabila Rasha; Arizul Suwar; T. Nazarullah T. Nazarullah (Economia: Journal of Economics and Management, 2025)
This article aims to analyze the internalization of the concepts of justice and maslahah in economic education as an effort to develop a learning paradigm that is oriented not only toward efficiency and growth, but also toward ethical values and social benefit. This study employs a qualitative approach based on a literature review, examining works in Islamic economics, philosophy of education, and curriculum theory. The findings indicate that the concept of justice in Islamic economic thought encompasses proportional distribution, the avoidance of exploitation, and the balanced fulfillment of rights and obligations. Meanwhile, maslahah emphasizes the orientation of economic policies and activities toward sustainable collective welfare. The internalization of these concepts in economic education can be implemented through value integration within the curriculum, reflective learning approaches, and the strengthening of moral dimensions in economic case analysis. This article argues that an economic education grounded in justice and maslahah has the potential to produce graduates who are not only technically competent but also ethically sensitive and socially responsible in economic practice. Abstrak Artikel ini bertujuan menganalisis internalisasi konsep keadilan dan maslahah dalam pendidikan ekonomi sebagai upaya membangun paradigma pembelajaran yang tidak hanya berorientasi pada efisiensi dan pertumbuhan, tetapi juga pada dimensi etika dan kebermanfaatan sosial. Penelitian ini menggunakan pendekatan kualitatif berbasis kajian pustaka dengan menelaah literatur ekonomi Islam, filsafat pendidikan, dan teori kurikulum. Hasil kajian menunjukkan bahwa konsep keadilan dalam perspektif ekonomi Islam mencakup distribusi yang proporsional, penghindaran eksploitasi, serta penegakan hak dan kewajiban secara seimbang. Sementara itu, maslahah menekankan orientasi kebijakan dan aktivitas ekonomi pada kemanfaatan kolektif yang berkelanjutan. Internalisasi kedua konsep tersebut dalam pendidikan ekonomi dapat dilakukan melalui integrasi nilai dalam kurikulum, pendekatan pembelajaran reflektif, serta penguatan dimensi moral dalam analisis kasus ekonomi. Artikel ini menegaskan bahwa pendidikan ekonomi yang berbasis keadilan dan maslahah berpotensi membentuk lulusan yang tidak hanya kompeten secara teknis, tetapi juga memiliki sensitivitas etis dan tanggung jawab sosial dalam praktik ekonomi.